Consensus views on implementation and measurement of enhanced recovery after surgery in England: Delphi study. Issue 6 (12th December 2012) - Knott, Amy; Pathak, Samir; McGrath, John S; Kennedy, Robin; Horgan, Alan; Mythen, Monty; Carter, Fiona; Francis, Nader K
Abstract : Objective: The Department of Health's Enhanced Recovery Partnership Programme (ERPP) started a spread and adoption scheme of Enhanced Recovery After Surgery (ERAS) throughout England. In preparation for widespread adoption the ERPP wished to obtain expert consensus on appropriate outcome measures for ERAS, emerging techniques being widely adopted and proposed methods for the continued development and sustainability of ERAS in the National Health Service. The aim of this study was to interrogate expert opinion and define areas of consensus on these issues. Design: A Delphi technique using three rounds of reiterative questionnaires was used to obtain consensus. Participants: Experts were chosen from teams with experience of delivering a successful ERAS programme across different surgical specialties and across various disciplines. Setting: The first two rounds of the questionnaire were completed online and a final, third round was undertaken in a meeting using interactive voting. Results: 86 experts took part in this study. Consensus statements agreed that patient experience data should be recorded, analysed and reviewed at regular ERAS meetings. Recent developments in regional analgesia, the increased use of intraoperative monitoring for fluid management and cardio-pulmonary exercise testing were the main emerging techniques identified. National standards for those outcome measures would be welcomed. To sustain success in ERAS, the experts highlighted clinical champions and the presence of a dedicated ERAS facilitator as essential elements. For future networking, a unanimous agreement was achieved on the formation a national network to facilitate spread and adoption of ERAS and to promote research and education across surgery. Conclusions: Consensus was achieved on regular measurement and review of patient experience in ERAS. Agreement was reached on the role of regional analgesia and the use of oesophageal Doppler for intraoperative goal-directed fluid therapy. In order to facilitate the further spread and adoption of best practices and to promote research and education, an ERAS-UK network was recommended.